Archivo fotográfico colectivo y paisaje migrante: la experiencia de los dekasegi latinoamericanos en el Japón periurbano - Ibañez Sandoval, Marita (2024)
This paper delves into the experiences of the Latin American dekasegi community within the peri-urban landscapes of Japan, specifically in a city in Ibaraki prefecture. The surrounding landscape is documented using participatory visual methods based on photographic practice, such as photowalks and photo elicitation. By exploring the intersection of visual communication, migrant identities, and cross-cultural processes to document the migratory landscape, this study reveals how photography and its participatory use are means to construct and preserve individual and collective memories and generate transparent conversations about the migrant experience. A collective photographic archive from the photowalks in Jōsō offers an insight into transculturality in the Japanese peri-urban landscape, enriching the academic understanding of migration and visual culture. This study emphasizes the importance of participatory visual methods in migration research and the role of photography in the recognition and appreciation of migrant identities and narratives.